Gesundheit und Bewegung - Löllgen H; Börjesson M; Cummiskey J; Bachl N; Debruyne A (Deutsche Zeitschrift für Sportmedizin, 2015)
Goals of pre-participation examination (PPE)in athletes are primarily to protect health of athletes. This applies for children, adolescents, leisure time and top athletes.To recognise early possible risks, history and clinical examination is agreed to be the basis of PPE. However, there is a long-standing controversy about whether ECG at rest should also be mandatory for all athletes. ECG is rejected in the US but included in most European countries. In addition, some large sports organisations also requireECG in PPE of athletes. The resting ECG can detect potential life-threatening diseases such as cardiomyopathies or ion-channel diseases, thus avoiding sudden cardiac events or even death. The present paper discusses many arguments pro and contra ECG in athletes screening. Arguments against are organisational problems, as sports physicians are not present nationwide in the US. Main arguments against are the lack of large prospective studies demonstrating reduced mortality by ECG, and the low sensitivity, specificity and predictive values of the ECG. However, current studies,new stringent and reliable criteria for ECG interpretation (e.g. Seattle criteria) increased the validity: false positive and negative findings decrease significantly. This is also supported by new, athlete-related ECG interpretation software in ECG devices, which are more reliable than visual analysis. This also may reduce legal problems, whereas psychological problems are of low importance as has been shown recently. Therefore, ECG recording in all athletes is strongly recommended in Europe. ECG is superior to history and clinical exam in detecting hidden and congenital diseases. However, special education in sports cardiologyis advised, courses and training in ECG interpretation in athletes, as well as special ECG devices are mandatory for correct ECG interpretation in athletes.KEY WORDS:ECG, Athlete, Pre-Participation Examination, PC-Analysis of ECG, Sports Cardiology